2006
DOI: 10.1111/j.1440-1746.2005.04086.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of non‐alcoholic fatty liver disease among Korean adults

Abstract: These results demonstrate that the prevalence of NAFLD in Korean adults, according to sonographic surveys, is comparable to that seen in more developed countries. From the perspective of increasing obesity, the high prevalence rates noted in the study may herald an increased burden of chronic liver disease in the Korean population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
238
6
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(280 citation statements)
references
References 32 publications
27
238
6
9
Order By: Relevance
“…48,49 This is in sharp contrast to Asian studies where the mean BMI is about 29 Kg/m 2 in India 53,54 ; 24 in Korea, 17 27 in Sri Lanka, 55 23 in China, 52 and 23 in Japan. 19 Initial studies from India that used the international criteria 56 for defining overweight and obesity found obesity in only 12-30% of patients 57,58 compared with 30-100% in Western studies depending on the population studied.…”
Section: Overweight/obesitycontrasting
confidence: 47%
See 2 more Smart Citations
“…48,49 This is in sharp contrast to Asian studies where the mean BMI is about 29 Kg/m 2 in India 53,54 ; 24 in Korea, 17 27 in Sri Lanka, 55 23 in China, 52 and 23 in Japan. 19 Initial studies from India that used the international criteria 56 for defining overweight and obesity found obesity in only 12-30% of patients 57,58 compared with 30-100% in Western studies depending on the population studied.…”
Section: Overweight/obesitycontrasting
confidence: 47%
“…19 Data from other Asian countries show that the prevalence of fatty liver was higher in males being 13.3% and 2.7%, respectively, in males and females in China, 52 and 21.6% and 11.2%, respectively, in Korea. 17 The reason for this difference in gender distribution could be linked in part to the difference in lifestyles of women in Western and Eastern settings, but the role of a genetic predisposition in the Asian men seems likely given the recent discovery of the role of APO C3 polymorphisms in the Asian Indian men with NAFLD.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendation is made with less certainty, higher cost or resource consumption Quality of Evidence High [A] Further research is unlikely to change confidence in the estimate of the clinical effect Moderate [B] Further research may change confidence in the estimate of the clinical effect Low [C] Further research is very likely to impact confidence on the estimate of clinical effect studies have shown that the prevalence of NAFLD increases with age. [24][25][26][27][28] The likelihood of disease progression to advanced fibrosis or mortality increases in older patients with NAFLD. [29][30][31] Many recent studies have reported that male gender is a risk factor for fatty liver disease.…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…Aging is also associated with increased lipid accumulation in nonadipose tissues, including the liver. Previous studies reported that aging increases the prevalence rates of the metabolic syndrome and non-alcoholic fatty liver disease (NAFLD) in human (Park et al 2006;Amarapurkar et al 2007). Generally, the prevalence rate of the NAFLD among adults is estimated at 15-30 %, whereas overall prevalence rate of NAFLD among elderly people aged more than 65 years was 35.1 % (Amarapurkar et al 2007;Chalasani et al 2012;Koehler et al 2012).…”
Section: Introductionmentioning
confidence: 99%